Factors affecting the number of banking loans during the covid-19 pandemic (empire study on Indonesian conventional commercial banks in 2020-2021) - Ni Nyoman Dwi Anjani Putri Ni Nyoman Dwi Anjani Putri; Ki Agus Andi; Niken Kusumawardani (Asian Journal of Economics and Business Management, 2022)
This article discusses the factors that affect the amount of bank credit during the covid-19 pandemic. The decline in the number of loans disbursed in early 2020 led to overall economic instability. This phenomenon has sparked interest in researching factors affecting the amount of credit to provide solutions to the problems faced. Unlike previous research, this research focused on the amount of credit disbursed during the Covid-19 pandemic. In addition, this study also used all samples of conventional commercial banks registered with financial services authorities in Indonesia. The data used are banking financial reports in 2020 and 2021. This study analyzes banking performance as measured by the ratio of CAR, OEOI, LDR, NIM, and ROA whether or not it affects the amount of credit disbursed during the Covid-19 pandemic. The research method used is a test of classic assumptions and multiple linear regression analysis. The analysis results show that CAR, NIM, and ROA significantly positively affect the amount of credit distributed. Meanwhile, the LDR significantly negatively affects the amount of credit disbursed. These four variables affect the amount of credit disbursed by the bank. Bank management must pay attention to banking performance, especially the ratio of CAR, NIM, ROA and LDR so that the role of banks in disbursing loans remains optimal during the Covid-19 pandemic. The limitation in this study is that the number of variables studied is only 5 that have not shown a major influence in influencing the amount of credit disbursed. Further research is expected to examine many variables that show a large influence on the amount of credit disbursed to provide solutions for banks in increasing the amount of credit.